Effectiveness of Discovery Learning Approaches integrated with Task Group Guidance to Increase Student Confidence in Guidance and Counseling - Asradi Asradi; Freddy Sarman (Bulletin of Social Studies and Community Development, 2022)
Abstract: This study aims to find out and prove the use of the Discovery Learning approach through group guidance services to increase self-confidence. The hypothesis proposed in this study is that there is a change or increase in students' confidence after being given the treatment of group guidance services using discovery learning approaches in task topic group guidance services. This study uses quantitative methods. This type of research is pre-experiment, using the one group pretest posttest design. Selection of subjects using purposive sampling method. The number of research subjects was ten people with low self-confidence categories. This research was carried out in the guidance and counseling study program, the instrument used was the scale of confidence with a Likert scale model. Data were analyzed using nonparametric statistical techniques that used the Wilcoxon Signed Ranks Test. The results showed that the pretest score was 77.5 and posttest 101.8. Then to test the hypothesis obtained Asymp results. Sig. (2-tailed) 0.005 less than 0.005, thus Ho can be interpreted rejected and Ha accepted, it was concluded that there was a change or an increase in students' self-confidence after being given the treatment of group guidance services using the discovery learning approach. Keywords: group guidance, discovery learning, self-confidence.